The Influence of Service and Product Quality on Customer Satisfaction (A Case Study at Geprek Mas Boy Pagar Alam, Rajabasa District, Bandar Lampung City) - Rico Ricardo; Iskandar Ali Alam (Indonesian Journal Economic Review (IJER), 2026)
In fulfilling human needs and responding to the competitive challenges of business activities, a well-directed and targeted market segmentation innovation is required. This can be achieved by implementing a carefully planned marketing mix strategy covering aspects of product, service, distribution, and promotion. Business potential in product marketing is always influenced by surrounding external factors and conditions. In this case, the phenomenon occurring at Geprek Mas Boy is the inadequate service provided to consumers, while the quality of the products served has still received negative evaluations from several customers. This is reflected in the Google ratings received by Geprek Mas Boy, which scored 3.8 out of 5.0. This study involved 63 respondents who completed the questionnaire. The results of this research are: 1) SPSS testing showed that the t-count value for service quality was 0.745 with a significance probability of 0.459. 2) SPSS testing showed that the t-count value for product quality was 4.598 with a significance probability of 0.001. This means that both variables have a positive and significant effect on customer satisfaction.